Kill show : a true crime novel - Sweren-Becker, Daniel (Harper, 2023)
"When sixteen-year-old Sara Parcell goes missing, it's an utter tragedy . . . and an entertaining national obsession in this thoughtful and addictively readable novel that offers a fresh and provocative take on whodunits and true crime. Sixteen-year-old Sara Parcell disappeared without a trace on a crisp April morning in Frederick, Maryland. Her tragic story was a national obsession and the centerpiece of a controversial TV docu-series that followed her disappearance in real time. But is it possible that everyone missed the biggest secret of all? Ten years after the events in question, the people who knew Sara best are finally ready to talk. In this genre-bending novel, Daniel Sweren-Becker fashions an oral history around the seemingly familiar crime of a teenage girl gone missing. Yet Kill Show, filled with diabolical twists and provocative social commentary, is no standard mystery; through "interviews" with family members, neighbors, law enforcement, TV executives, and a host of other compelling characters, Sweren-Becker constructs a riveting tale about one family's tragedy... and Hollywood's insatiable desire to exploit that tragedy. By revealing the seedy underbelly of the True Crime entertainment machine, Kill Show probes literary territory beyond the bounds of the standard whodunit-it's a thoughtful exploration into America's obsession with the mysteries, cold cases, and violent tales we turn to for comfort. Groundbreaking, fast-moving and informed, this is a novel about who's really responsible for the tragedies we love to consume"--